Marine Waste Management Based on Smart Environment in ASEAN: A Comparative Analysis of the Philippines, Indonesia, and Malaysia - Nazhatul Izzah; Muji Mulia; Putri Marzaniar (JURNAL ILMIAH ILMU ADMINISTRASI, 2026)
The problem of marine debris in the ASEAN region is becoming increasingly urgent due to population growth, urbanization, and high plastic consumption. This study compares marine debris management policies and strategies in Indonesia, Malaysia, and the Philippines using the Smart Environment approach, a technology-based, intelligent, and sustainable environmental management approach. Using a systematic literature review, the study examines national regulations, management systems, and technological innovations in each country. Preliminary results indicate that implementing the Smart Environment concept through the development of waste management, energy management, and sustainable resource management has significant potential for reducing environmental impacts. This study aims to provide data- and technology-based policy recommendations to strengthen integrated marine debris management in the ASEAN region.